Room temperature coherently coupled exciton-polaritons in two-dimensional organic-inorganic perovskite - Wang, Jun (2020)
Two-dimensional (2D) organic–inorganic perovskite semiconductors with natural multiquantum well structures and confined 2D excitons are intriguing for the study of strong exciton–photon coupling, due to their large exciton binding energy and oscillation strength. This strong coupling leads to a formation of the half-light half-matter bosonic quasiparticle called exciton–polariton, consisting of a linear superposition state between photonic and excitonic states. Here, we demonstrate room temperature strong coupling in exfoliated wavelength-tunable 2D organic–inorganic perovskite semiconductors embedded into a planar microcavity, exhibiting large energetic splitting-to-line width ratios (>34.2). Angular-dependent spectroscopy measurements reveal that hybridized polariton states act as an ultrafast and reversible energy oscillation, involving 2D perovskite exciton, cavity modes (CM), and Bragg modes of the distributed Bragg reflector. Meanwhile, sizable hybrid particles dominantly couple to the measured optical field through the CMs. Our findings advocate a considerable promise of 2D organic–inorganic perovskite to explore fundamental quantum phenomena such as Bose–Einstein condensation, superfluidity, and exciton–polariton networks.